2020
DOI: 10.18203/2319-2003.ijbcp20203522
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication during COVID-19 outbreak: a cross sectional online survey in Dhaka city

Abstract: Background: Self-medication is a common practice in Bangladesh as it provides a low-cost alternative for people, which involves inappropriate and injudicious use of medicines treat self-recognized symptoms by the people.Methods: A cross sectional online survey was conducted on 626 citizens by structured questionnaires during COVID-19 outbreak from April to May 2020 in Dhaka city, to observe the prevalence, pattern and sources of self-medication among the respondents with high socio-economic standings and educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
102
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 13 publications
21
102
4
4
Order By: Relevance
“…The total score was calculated by summing the raw scores of each item ranging from 0-27, with a higher score indicating greater severity of depression. The levels of depressive symptoms were classified into five groups according to their score as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). In the present study, the PHQ-9 scale was found to have Cronbach's α of 0.86.…”
Section: Patient Health Questionnaire (Phq-9) Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The total score was calculated by summing the raw scores of each item ranging from 0-27, with a higher score indicating greater severity of depression. The levels of depressive symptoms were classified into five groups according to their score as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). In the present study, the PHQ-9 scale was found to have Cronbach's α of 0.86.…”
Section: Patient Health Questionnaire (Phq-9) Scalementioning
confidence: 99%
“…Factors that have been shown to influence self-medication include previous experience with a disease or a symptom, availability of medicine, increasing costs of prescription drugs, and the willingness of people to empower themselves [ 19 , 20 ]. In Bangladesh, self-medication is influenced largely by socioeconomic status, educational attainment, and lack of proper knowledge [ 21 ]. Although the World Health Organization (WHO) advocates self-medication for inhibiting and treating minor health problems at minimal cost, in severe cases, it may lead to adverse health outcomes, including higher mortality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…in ICUs and other highrisk units. • Possible increased self-medication with antibiotics in some countries or regions of the world [48] • Possible decreased antibiotic consumption because of fewer patient consultations, e.g. for self-limiting infections that would otherwise have resulted in an antibiotic prescription [4] • Possible decreased incidence of respiratory tract infections as a consequence of decreased personto-person transmission because of lockdowns, resulting in decreased antibiotic consumption…”
Section: Type Of Factormentioning
confidence: 99%
“…But the critical consideration of oxygen therapy is inevitable in almost every patient treated in ICU. As stated in the National Guideline on case management of COVID-19 in Bangladesh, there is no precise effective treatment for COVID-19, the main stay of management is early diagnosis and supportive care of symptoms and optimum support for organ function in severe illness [10]. No drug is yet recommended as chemoprophylaxis as there is no quality evidence of efficacy and safety in COVID-19.…”
Section: Introductionmentioning
confidence: 99%